’’المواھب اللدنیۃ با لمنح المحمدیۃﷺ’’ کا تعارفی و تجزیاتی مطالعہ: An Analytical study of the "Al-Mawāhib Al-Laduniyat Bil Minḥ Al-Muhammadiyah" - Nawaz, Muhammad; Fazal Haq Turābī, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
Although Imam Qusṭalānī, in compiling his book "Al-Mawāhib Al-Laduniyat Bil Minḥ Al-Muhammadiyah", has followed the footsteps of Qazi Ayaz’s book Al- Shifā. But many chapters and information are unique to them and he has expanded this book with his additions and made it a treasure trove of information. This book is a beautiful fusion of the traditions of Muhaddithin and Ahl-e-Siyyar. Because he was not only a muhaddith but also a biographer. Were his greatest service in the learning of Hadith is "Irshad Al-Sārī Sharh Saḥiḥ Bukhārī", there his most significant service in Sira is this book. He has used the traditions of both the narrators and the Biographers in compiling it. In this book, the locks of meanings are opened with the keys of Fatḥ Al-Bārī Li Ibn-e-Hajar ‘Asqalānī. In other words, he has benefited a lot from Fatḥ Al-Bārī Sharḥ Bukhari and has gained a lot of confidence. A large number of scholars have used this book, including Shiblī Nu‘mānī, who has made extensive use of it in his Sirat un-Nabiﷺ . Due to its popularity, many of its rates have been written. The most detailed of these is the Zurqānī rate of Qusṭalānī. The great scholar like Imam Zarqani has commented in eleven volumes of this book, which is proof of its authenticity, noteworthy, and worth reading and treasure. Sheikh Nūruddin Ṭrabulsī gave Sharh and great people like Safiuddin Qasashi, Burhanuddin Ibrahim Maimoni, Shamsuddin Muhammad Shobri Misri and Nooruddin Ali Qari embellished this book with their footnotes. On the one hand, it teaches love and respect for the Holy Prophet ﷺ and on the other hand, it mentions the rights of the Holy Prophet ﷺ and the rewards for their payment. The writing style of the book is simple and smooth as well as eloquent and eloquent. The temptation is not so long that the length will be too long for the reader, nor is it so short that access to the concepts and demands will not be possible due to the brevity. The book has been read by the people and it has been adopted by biographers as an authentic and reliable source. Because of its importance and usefulness, an introductory and analytical study of this book will be presented in this article.